2001
DOI: 10.1002/mrd.1047
|View full text |Cite
|
Sign up to set email alerts
|

Testicular protein Spag5 has similarity to mitotic spindle protein Deepest and binds outer dense fiber protein Odf1

Abstract: Outer dense fibers (ODF) and the fibrous sheath (FS) are major cytoskeletal structures in the mammalian sperm tail. The molecular mechanisms underlying their morphogenesis along the axoneme or their function are poorly understood. Recently, we reported the cloning and characterization of Odf2, a major ODF protein, and Spag4, an axoneme-binding protein, by virtue of their strong interaction with Odf1, the 27 kDa major ODF protein. We proposed a crucial role for leucine zippers in molecular interactions during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 19 publications
1
59
0
5
Order By: Relevance
“…A kinase possibly involved early in the DNA damage response. In the testis is expressed at the beginning of the meiotic phase (Arama et al, 1998;Letwin et al, 1992 (Shao et al, 2001) Spermatogonial markers 1428639_at 0.58 Lin9 Required for the expression of the spermatogonial marker B-Myb (Latham et al, 1996;Pilkinton et al, 2007) 1422655_at 0.57 Ptch2 Patched homolog 2. A receptor for sonic hedgehog, expressed in spermatogonia, and at lower levels in spermatocytes (Szczepny et al, 2006) [no specific references are given for these genes, since description of their metabolic function can be found in the free databases at the link http://www.informatics.jax.org].…”
Section: Metabolismmentioning
confidence: 99%
“…A kinase possibly involved early in the DNA damage response. In the testis is expressed at the beginning of the meiotic phase (Arama et al, 1998;Letwin et al, 1992 (Shao et al, 2001) Spermatogonial markers 1428639_at 0.58 Lin9 Required for the expression of the spermatogonial marker B-Myb (Latham et al, 1996;Pilkinton et al, 2007) 1422655_at 0.57 Ptch2 Patched homolog 2. A receptor for sonic hedgehog, expressed in spermatogonia, and at lower levels in spermatocytes (Szczepny et al, 2006) [no specific references are given for these genes, since description of their metabolic function can be found in the free databases at the link http://www.informatics.jax.org].…”
Section: Metabolismmentioning
confidence: 99%
“…Indeed, deletion of the ODF1 leucine zipper significantly reduced binding (20-fold) to KLC3. We had previously determined that the ODF1 leucine zipper is crucial for the association with ODF2 (29); SPAG4, a spermatid-specific axonemebinding protein (30); and SPAG5 (31,58). The specificity of these leucine zipper-mediated interactions is underscored by our observation that KLC3 does not bind to ODF2 even though ODF2 contains two functional leucine zipper motifs (29,59).…”
Section: Table I Klc3 Binding To Odf1 In Yeastmentioning
confidence: 92%
“…A previous study showed that binding partners of the N-terminal leucine zipper motif of ODF1 containing one or two leucine zipper motifs (Shao et al 2001). TCP11a and TCP11c proteins are of 441 and 440 amino acids, and they have the same C-terminal 426 amino acids.…”
Section: Odf1 Is a Tcp11-binding Partner And Leucine Zipper Is Essenmentioning
confidence: 99%